EFFECT OF USING VIDEO ON THE ABILITY OF EIGHTH GRADE STUDENTS TO UNDERSTAND GRAPHICAL SYMBOLS - İsmail Yavuz ÖZTÜRK; Kemalettin DENİZ (International Journal of Eurasia Social Sciences, 2018)
Graphical symbols are one of the coding systems that people often encounter in everyday life. In addition to being able to perceived quickly and easily, the ability to remove language barriers allows graphical symbols to be used in the communication process. These symbols which have functions such as informing, directing; reporting actions to be done, warning, instructing, against dangerous health-threatening situtations are obliged to be used in schools in Turkey by a circular issued by the Ministry of National Education in 2014. However, it is thought that there are shortcomings in the teaching of graphical symbols. Because these have been found that the achievements related to the teaching of graphical symbols in the curricula that form the bais of educational activities are insufficient and the relevant achievement of this subject is not included after the fourth class in the curricula of Turkish lesson which aims to train especially individuals as effective communicaters especially. Thus, learning of the meanings of these symbols by the students has been system-free and left the chance from the fifth class onwards. For this reason, it is aimed to reveal the level of understanding messages send by graphical symbols and to make a study that would compensate for missing learning of students who study at the fifth and upper classes. An activity was conducted in which a single group pre-test and post test pattern method was used with 58 students studying in eight class of Alata Secondary School in Erdemli district of Mersin within this context. At the beginning of the process, “Matching Questions for Understanding the Messages of Graphical Symbols Correctly” has been applied as pre-test to the students. A video had been prepared by the researcher and which contains the importance, purpose of using and the meanings of graphical symbols they encounter in their schools and products they buy from school canteen was showed after the test. Finally the matching questions were applied to the students again as post test. Answers of the students were analyzed with the SPSS 25 package program. In findings, these have been found that the students were not aware of the meanings of all the graphical symbols they already met but the activity based on the prepared video developed the skills of understanding the messages of graphical symbols correctly. It is thought that these study conducted could provide data for those who will research on visual reading, in particular teaching of graphical symbols.